(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Gastric issues that accompany the use of NSAIDs (Non-steroid anti-inflammatory drugs) are always a serious global concern. The inhibition of the Cycloxygenase enzyme (COX) limits the prostaglandin synthesis and thereby facilitates the control of pains, inflammation etc. But this creates gastric issues due to the reduction of mucin formation in the stomach. The present work was performed to create a modification in the structure of NSAID drug Diflunisal, to reduce the gastric effect of acidic moiety in the structure and elevate the overall biological properties. The drug Tromethamine, a base used in acidosis treatment was substituted to reduce the acidic issues. The heterocyclic compound pyrrole was substituted to elevate the properties. Neutral, salt, amide and ester combinations of Tromethamine-Diflunisal were designed, optimized and docked to the crystal structures of COX-1 (PDB ID: 6Y3C) and COX-2 (PDB ID: 5IKR) enzymes, using PyRx software. The combinations with lower COX-1 and COX-2 binding energies relative to Diflunisal were noted. It was analysed if the combinations of Diflunisal, Tromethamine and pyrrole lowers drug-properties or induce toxicities. Pyrrole substitution at position R4 was not found favourable for COX binding. Among the favourable combinations, DF19 is the Diflunisal-Pyrrole-Tromethamine combination, equally favourable for binding to COX targets.